The Role of Serum Procalcitonin, Interleukin-6, and Fibrinogen Levels in Differential Diagnosis of Diabetic Foot Ulcer Infection - Pınar Korkmaz; Havva Koçak; Kevser Onbaşı; Polat Biçici; Ahmet Özmen; Cemile Uyar; Duru Mıstanoğlu Özatağ (Journal of Diabetes Research)
Aims. We aimed to evaluate the roles of interleukin-6 (IL-6), PCT, and fibrinogen levels in the differential diagnosis of the patients with infected diabetic foot ulcer (IDFU) and noninfected diabetic foot ulcer (NIDFU) and to compare those with C-reactive protein (CRP), white blood cell (WBC), and erythrocyte sedimentation rate (ESR). Methods. Patients over 18 years with a diagnosis of type 2 diabetes mellitus and DFU who were followed up in our hospital between 1 January 2016 and 1 January 2017 were included in the study. In addition to this patient group, patients with diabetes but without DFU were determined as the control group. Results. Thirty-eight patients with IDFU, 38 patients with NIDFU, and 43 patients as the control group were included in the study. Fifty-six point three percent of the patients who participated in the study were males, and the mean age was 61.07 ± 11.04 years. WBC, ESR, CRP, IL-6, and fibrinogen levels of the cases with IDFU were determined to be significantly higher compared to the cases in NIDFU (p<0.01). The area under the ROC curve (AUROC) value was highest for CRP (0.998; p<0.001), and the best cut-off value for CRP was 28 m/L. The best cut-off values for fibrinogen, IL-6, ESR, and WBC were 480 mg/dL, 105.8 pg/mL, 31 mm/h, and 11.6 (103 μ/L), respectively. Conclusion. Serum PCT levels were not found to be effective in the discrimination of IDFU and NIDFU. Serum IL-6 and fibrinogen levels seem to be two promising inflammatory markers in the discrimination of IDFU.